Potential of preimplantation genomic selection using the blastomere separation technique in bovine in vitro fertilized embryos - Takashi FUJII; Akira NAITO; Satoru MORIYASU; Soichi KAGEYAMA (The Society for Reproduction and Development, 2021)
Preimplantation genomic selection combined with an in vitro embryo production system is expected as a means of accelerating genetic improvement in cattle. While micromanipulation-based biopsy approaches are often used to collect embryonic cells for genetic testing, they require expensive equipment and sophisticated skills, hindering the adoption of this system. In the present study, to develop a simple method for preimplantation genomic selection using the blastomere separation (BS) technique in bovine in vitro fertilized embryos, we examined the accuracy of single nucleotide polymorphism (SNP) genotyping and optimal cryopreservation method in demi-blastocysts produced by the BS technique. We demonstrated reliable SNP genotyping using DNA derived from demi-blastocysts. We indicated a suitable equilibrium time in vitrification solution for demi-blastocysts and succeeded obtaining pregnancies by the transfer of vitrified demi-blastocysts. In conclusion, our findings suggest that the BS technique provides a simple method for preimplantation genomic selection in bovine in vitro fertilized embryos.